THE ACT OF SALE OF A POSTPARTUM CHILD BY THE CHILD’S BIRTH MOTHER - Thamrin, Muhammad Arganata; Ismail, Affero (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
Children are the next generation and determinants of the future of the nation as well as a mirror of life attitudes in the future. Therefore, they need to get the opportunity to grow and develop their physical need, mental and social skill properly. However, sometimes they face serious problem such as getting pregnant out of wedlock when they are 13 years old. The problem occurs because of something undesirable and for that reason they are not ready to become parents. Thus, they commit acts of minor trafficking that are contrary to the provisions of the article 76f juncto Article 83 of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. Minor trafficking is a crime that violates human rights, whose perpetrators are not only adults but also children and most of them are victims of criminal acts. The minors who commited criminal acts need to be taken seriously and their criminal liability is different from adults. Therefore, the minors who are in conflict with the law still get specifically protection regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System.